Respostas
respondido por:
0
a80 = a1 + 79r
a80 = - 3 + 79(5)
a80 = - 3 + 395
a80 = 392
Sn = (a1 + an).n
-----------------
2
Sn = (- 3 + 392).80
---------------------
2
Sn = 389 . 40
Sn = 15560
a80 = - 3 + 79(5)
a80 = - 3 + 395
a80 = 392
Sn = (a1 + an).n
-----------------
2
Sn = (- 3 + 392).80
---------------------
2
Sn = 389 . 40
Sn = 15560
respondido por:
0
resolução!
r = a2 - a1
r = 2 - (-3)
r = 5
a80 = a1 + 79r
a80 = - 3 + 79 * 5
a80 = - 3 + 395
a80 = 392
Sn = ( a1 + an ) n / 2
Sn = ( - 3 + 392 ) 80 / 2
Sn = 389 * 40
Sn = 15560
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás